Satisfação conjugal e aspectos relacionados: a influência da comunicação, da semelhança de atitudes e da percepção interpessoal - Miranda, Ericé da Silva (1986)
The objective of this research was to analyse the correlations among Marital Satisfaction and three relevants aspects of a diadic relation, namely Self-disclosure, Interpersonal Perception and Similarity of Attitudes. The influences of some others variables (as age years of Marriage, self-esteem, income, education, and number of chi1dren) were as we11 examined. It was also analysed, in our cultural environment, some of Dr. Susan Singer Hendrick's findings in the USA. Analysing marriage historically -and also others pertinent factors - a model was proposed for the assessment of Marital Satisfaction and some others associated phenomena. Marital Satisfaction was examinedbtiefly under two theories: the 'exchange' and the 'equity' ones. In the theoretical part of the study it was made a review of Marital Satisfaction studie's, that tried to correlate such variable with many others. When formulated the problem it was intended to show the possible relation among three selected variables and Marital Satisfaction. There is no report about such a study in Brazil - hence the pioneer character invoked. To test the theoretica1 proposition, data were gathered from a samp1e of forty-eight coup1es (Persons with different ages, working areas, education, etc, all of them living at Rio de Janeiro County). The resu1ts showed Interpersona1 Perception and Self-esteem as the most important variables. One can conclude also, that women, perhaps by the influence of socio-cultural forces, place themselves at a lower level within a conjugal relation.